From Form to Words: Knowledge Transfer Vehicles in Late-20th-century Portuguese Modern Architecture - Agarez, R. (History of Construction Cultures. 7ICCH – Seventh International Congress on Construction History, 2021)
Design and construction statements (“memórias descritivas”) have been mandatory for every building permit application in Portugal since 1909. By the mid-20th century these bureaucratic documents had become essential means of expression for designers, architects, and non-architects, to convey arguments: functional and technical, but also their design philosophy and understanding of site and context, down to the proposal’s zeitgeist, local traditions and particular circumstances. This paper draws on a selection of design statements written for works produced in Portugal between the 1950s and 1970s, interrogating their potential as fundamental knowledge transfer devices for designers to articulate, test and communicate their ideas as well as their take on new techniques and concepts. While these writings seldom contain comprehensive theoretical arguments, I suggest they nevertheless outline their authors’ intellectual understanding of built environment creation processes, showing how (internationally) discussed ideas percolated into built artefacts and how their words complemented their form-creation process.